Commercial applicator licenses - do you need one? - Skoglund, L. G., author; McDonald, S. K., author; Colorado Environmental Pesticide Education Program, publisher (Colorado State University. Libraries, 2006)
Pesticide Applicators Act, State of Colorado Title 35 Article 10. This Act provides for licensing of individuals and businesses involved in pesticide application.
CEPEP 10/01, updated 6/06.
PLEASE NOTE: This fact sheet is a historical document and some information may not reflect current federal and state laws and regulations and best practices.
Keywords: Pesticide applicators (Persons) -- Licenses -- Colorado; Pesticides -- Application -- Colorado; Pesticides